Cyclodextrin-mediated micellar electrokinetic chromatography and matrix-assisted laser desorption/ionization time-of-flight mass spectrometry for the enantiomer separation of racemorphan in human urine - Ban, EM; Choi, SW; Lee, JA; Lho, DS; Yoo, YS (ELSEVIER SCIENCE BV, 1999)
Micellar electrokinetic chromatography (MEKC) was successfully and conveniently applied to the chiral separation with the addition of cyclodextrins (CDs) as chiral selector to the running buffer. Chiral separation depended on the type of CD; in particular, P-CD was effective for the chiral separation of racemorphan. We investigated the optimal conditions of type and concentration of CD as chiral selector for the routine enantiomeric separation of racemorphan with good reproducibility. The effects of other parameters such as buffer pH and detection wavelength were also investigated to obtain the optimum conditions for the enantiomeric separation of racemorphan. Matrix-assisted laser desorption/ionization time-of-flight mass spectrometry was used for confirmation of racemorphan. The optimal conditions for enantiomeric separation of the racemorphan were as follows: 50 mM berate buffer at pH 9.4 with 50 mM SDS, 10 mM beta-CD and 20% 1-propanol, 57 cmx50 mu m fused-silica capillary column, and UV detection at 192 nm. Based on the developed method, racemorphan in human urine was also separated and determined using solid-phase extraction and MEKC. (C) 1999 Elsevier Science B.V. All rights reserved.
Keywords: PERFORMANCE LIQUID-CHROMATOGRAPHY; CAPILLARY ZONE ELECTROPHORESIS; CHIRAL SEPARATION; THEORETICAL ASPECTS; DEXTROMETHORPHAN; DEXTRORPHAN; OXIDATION; MODEL